Prevalence of thyroid disorders in an out-patient department setting: a retrospective study - S., Krishneswari R.; Shaji, Navya Mariam; Maheshkum, Balakrishna ar S. (International Journal Of Community Medicine And Public Health, 2022)
Background: Disorders of the thyroid gland has become one of the most common endocrine diseases affecting the global population next to Diabetes Mellitus. Data available on the prevalence of thyroid disorders among Indian population is scanty. This study is aimed to investigate the prevalence of thyroid dysfunction in the local population visiting the endocrinology out-patient department of National Homoeopathy Research Institute in Mental Health, Kottayam. Methods: This is a hospital based retrospective descriptive analysis carried out among the patients attended in the endocrinology out-patient department of National Homoeopathy Research Institute in Mental Health (NHRIMH), Kottayam. Patients with Thyroid disorders who seek treatment from the endocrinology OPD for a period of six months (January 2021 to June 2021) were selected for this retrospective analysis. Results: Data were collected from the medical records department of NHRIMH and were analyzed based on the age, sex, different types of thyroid disorders and the medicines prescribed including potency. Conclusions: Females are commonly affected with thyroid disorders and the common age group is between 40 and 49 years. The most common thyroid disorder encountered is hypothyoidism and the most common medicine used is ‘thyroidinum’.